Application of Recommendations for Diagnosis of Diseases in the Field of Hematology and Oncology With Forward Chaining Algorithm - Abiel Filetus; Ricky Raymond; Prittania Friska Octavia; Halim Agung (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
The COVID-19 pandemic has made many changes in everything, both from the industrial world and human habits. Illness is one of the things that cannot be postponed in its completion, so that people can consult a doctor to be able to recognize the disease suffered by the community In the past, consultations had to come to the hospital, nowadays there are innovations in the field of Information Technology that make it easier for people to consult. The expert system is one of the fastest growing innovations. The expert system is one of the fastest growing innovations. Forward chaining is one of the algorithms of an expert system to get a conclusion through existing facts / data based on predetermined rules. Forward chaining can provide good disease conclusions with a 100% percentage of 30 diseases and 15 test cases. However, a diagnosis based on symptoms according to doctors only has a confidence level of 50-60%. So other assessment factors are needed to increase the percentage of these beliefs such as gender, age, medical history, supporting examinations, and others.